The Cost Behavior of Contemporary Accounting: Cost Stickiness and Reverse Cost - Vieira Fabre, Valkyrie; Borgert, Altair (Anais do Congresso Brasileiro de Custos - ABC, 2023)
The contemporary approach accounting, cost behavior is already an established theme in private sector literature, but it is still emerging when it comes to the public sector. When cost behavior is applied to different areas of accounting, the examples raise doubts. The issue of cost behavior has evolved from the traditional approach to accounting, to the contemporary approach. This study clarifies obscure aspects, unifies concepts, and presents a modern accounting classification of cost behavior, within the contemporary accounting approach. It is a theoretical research built on the deductive method, which provides a broader view of the implications of the evidence phenomena related to cost behavior and contributes to the development of future research with the same conceptual basis, regardless of the sample field of application. The cost behavior within the contemporary approach is something that should be developed in future research. To this end, clear definitions are needed that can guide researchers and be generalized to the different branches of accounting science. The rules for private and public accounting are different, and some similar terms have different concepts in the two sectors. Thus, this paper presents how the topic of cost behavior has evolved from traditional to contemporary approaches, the unification of concepts as part of the classification, and suggests how it can be interpreted. In the modern accounting classification of behavior the costs are symmetrical or asymmetrical, with cost stickiness phenome or reverse phenome. In the stickiness phenomenon, it is further classified with sticky effect or anti-sticky effect.